School related variables as correlates of performance in biology among senior secondary school students in Ibadan North Local Government Area of Oyo State, Nigeria (2014)
This study examines school related variables as con-elates of performance in Biology among senior secondary school students in Ibadan North Local Government Area of Oyo state. A sample of 286 students was randomly selected among thirteen secondary schools in Ibadan North Local Government Area of Oyo state. Four reliable measuring scales on school related factors were used as well as Performance in Biology test with reliability coefficient of 0.79. Three research questions were raised and analysed with Pearson Product Moment Correlation and Multiple Regression Analysis. A significant combined contribution of the independent variables (class size, peer influence, time management, laboratory facilities and study habit) to the prediction of performance in Biology was found. This suggests that the five independent variables combined accounted for 21.3% (Adj. R2= .213) variation in the prediction of performance in Biology. The study also shows that four out of five predictor variables (class size, time management, laboratory facilities and study habit) are potent predictors of performance in Biology. The most potent factor was study habit. This is followed by class size, laboratory facilities and time management. But peer influence is not a potent predictor of performance in Biology. This implies that an increase in study habit, lime management and laboratory facility will increase the tendency for an improved performance in Biology of the students. But the larger the class size, the lesser the tendency for an improved performance in Biology by the students. Among others, it was recommended that school teachers and school counselors or social workers should help students to develop a good study habit and time management which can be done through the organisation of seminars. Educational bodies and ministry of education should endorse the reduction and enforcement of appropriate teacher-students' ratio so as to enhance effective learning and conducive learning environment for better performance in Biology as a subject by the students.